408 Measures of metalworking fluid exposure and its relationship to respiratory health in machinists. (11th October 2013) - Peters, E; Arrandale,; Teschke,; Turner,; Chambers,; McLean,; Karlen,; Kennedy,
Abstract : Objectives: Our objective was to investigate the relationship between metalworking fluid (MWF) exposure and subsequent respiratory health among machinists in an inception cohort of apprentices. Methods: All first-year machinist apprentices at a provincial trade school were eligible to enrol (visit 1: 1988–1990). Subjects were retested during their 3 rd year (visit 2: 1990–1992) and again 16 years after baseline (visit 3: 2004–2006). Interviewers collected information on respiratory symptoms and personal, work and exposure histories. Questionnaire responses were used to model average MWF exposure intensity for each job. Duration and cumulative MWF exposure were subsequently estimated. Pulmonary function and bronchial hyper-responsiveness (BHR) were also measured. Multiple linear regression models were constructed to investigate the relationship between MWF exposure and both % predicted forced expiratory volume in 1 second (% P-FEV1) and BHR at visit 3. Results: At visit 1, 99 machinist apprentices were enrolled. At visit 3, 77 (77%) machinists participated; all were men (mean age 40.6 years). Machinists who had left the trade tended to have lower % P-FEV1 at visit 3 (p = 0.10) than current machinists and were more likely to have BHR (26% vs. 9%, p = 0.04). In regression models, leaving the machining trade was associated with lower % P - FEV1 at visit 3 (p = 0.005). Early MWF exposure was associated with lower % P - FEV1 at visit 3 (p = 0.02). In a separate model, current MWF exposure was associated with increased BHR (p = 0.05). Conclusions: Exposure to MWF was associated with % P-FEV1 and BHR at the 16 year follow-up. Early MWF exposure was associated with decreased % P-FEV1 and current exposure was associated with increased BHR. Machinists who left the trade had decreased % P-FEV1 and increased BHR at 16 year follow-up, demonstrating the strength of the healthy worker effect in this population and the need to account for this effect in studies of work-related respiratory disease.